Hemodynamic Analysis of a Microanastomosis Using Computational Fluid Dynamics - Yagi, Shunjiro; Sasaki, Takafumi; Fukuhara, Takahiro; Fujii, Kaori; Morita, Maki; Suyama, Yoshiko; Fukuoka, Kohei; Nishino, Teruyasu; Hisatome, Ichiro (YONAGO ACTA MEDICA, 2020)
[ABSTRACT] [Background] Technical issues in free flap transfer, such as the selection of recipient vessels and the positioning and method of anastomosis of the vascular pedicle, have been the subject of vigorous debate. Recent developments in computational fluid dynamics (CFD) have enabled the analysis of blood flow within microvessels. In this study, CFD was used to analyze hemodynamics in a microanastomosis. [Methods] In the fluid calculation process, the fluid domain modelizes microvessels with anastomosis. The inlet flow conditions were measured as venous waveform, and the fluid is simulated as blood. Streamlines (SL), wall shear stress (WSS), and oscillatory shear index (OSI) at the anastomosis were visualized and analyzed for observing effects from the flow field. [Results] Some flow disruption was evident as the SL passed over the sutures. The maximum recorded WSS was 13.37 Pa where the peak of a suture was exposed in the lumen. The local maximum value of the OSI was 0.182, recorded at the base of the anastomosis on the outflow side. [Conclusion] In the ideal anastomosis, the SL is disrupted as little as possible by the sutures. The WSS indicated that thrombus formation is unlikely to occur at suture peaks, but more likely to occur at the base of sutures, where the OSI is high. Tight suture knots are important in microanastomosis.